PENINGKATAN KOMPETENSI PEDAGOGIK GURU MELALUI PELATIHAN PAIKEM (PELATIHAN PADA GURU MI DAN MTS DI KABUPATEN CIANJUR) - Dewi, Laksmi (EDUTECH, 2014)
Abstract. Learning is not monopoly of teachers (teacher centered). The teacher in charge of teaching and, especially, the students who do learning activities, both have the same right to manage their learning process with its various components. Teachers should have the pedagogic skills makes the students learn. Pedagogical competence of teachers need to be trained to increase their skills, so that teachers are able to create an active learning, innovative, creative, effective and fun for students. Successful training is training that can provide added value to knowledge, attitudes and skills of the participants. Good training is training that suits participants needs and its results can be applied in paraticipants workplace. PAIKEM training which has been implemented successfully contribute to the improvement of pedagogical competence of the participants.Keywords: effective training, relevance, improving the competence of teachersAbstrak. Pembelajaran bukanlah monopoli guru (teacher centered). Guru yang bertugas mengajar dan, terutama, peserta didik yang melakukan kegiatan belajar, keduanya memiliki hak yang sama untuk mengelola proses pembelajaran dengan berbagai komponennya. Untuk itulah guru harus memiliki keterampilan pedagogik membuat siswa belajar. Kompetensi pedagogik guru perlu dilatih agar keterampilannya meningkat, sehingga guru mampu menciptakan pembelajaran yang aktif, inovatif, kreatif, efektif dan menyenangkan untuk peserta didik. Pelatihan yang berhasil adalah pelatihan yang dapat memberikan nilai tambah pada pengetahuan, sikap dan keterampilan peserta. Pelatihan yang baik adalah pelatihan yang sesuai dengan kebutuhan peserta dan hasilnya dapat diterapkan di dunia kerja peserta. Pelatihan PAIKEM yang telah dilaksanakan ini berhasil memberikan sumbangan bagi peningkatan kompetensi pedagogik para peserta.Kata Kunci : pelatihan efektif, relevansi, peningkatan kompetensi guru